Effect of Interactive Marketing Dimensions on Marketing Efficiency: Exploratory Study for the Opinions of a Sample of Employees of AsiaCell Mobile Telecommunications Company in Karbala City - Mahdi, Hawra Thamer; Salman, Fatima Abid Ali; Abd Ali, Nagham Dayek; Faez Hasan, Mohammed (Technium Social Sciences Journal, 2023)
The research dealt with the topic of interactive marketing in its dimensions (trust, commitment, interaction, two-way communication, quality of service, speed of response) and its impact on marketing efficiency in its dimensions (customer satisfaction, marketing costs, marketing research and development). The researchers sought to present a theoretical framework based on rooting Intellectual and making a modest contribution with regard to the variables and dimensions of the research, which was conducted in the Asia Cell Company for Mobile Communications, Holy Karbala Branch. And information, and a set of statistical methods were used in order to process data and information, namely: the arithmetic mean, standard deviation, Cronbach alpha test, coefficient of variation, Pearson correlation coefficient, interpretation coefficient, test (T), test (F), and in conclusion, the research reached A set of conclusions, the most important of which are: - The employees of Asia Cell Company realize the importance of building a long-term trust relationship with customers for the purpose of enhancing the company’s marketing efficiency. As well as all the correlations were positive and moral, which means that the company can benefit from the dimensions of interactive marketing to enhance marketing efficiency.